Pengaruh Intensitas Pengungkapan Dimensi Sustainability Reporting Terhadap Reaksi Pasar Perusahaan BUMN Yang Terdaftar Di BEI - Lestari, Made Linda; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2019)
This study aims to obtain empirical evidence to confirmed the effect of intensity disclosure on each aspect of sustainability reporting in BUMN companies which are listed on Indonesia Stock Exchange by the year 2013 until 2017. Determination of sample through the purposive sampling technique. There are 7 companies are being used as samples with 35 observation objects. The data were collected by documentation method. This research was using multiple linear regression analysis. Based on the analyzes result, environmental aspect has positive effect on the performance of companies which is reflected by the value of earnings per share (EPS). This result has meaning that the more environmental indicators were disclosed, the value of EPS on those companies will be more increasing. Whereas the result for economics aspect and social aspect shows that the intensity disclosure on those two aspectson sustainability reporting have no effect for the value of EPS. Keywords  :     Sustainability reporting, Economics Aspect, Environmental Aspect ,  Social Aspect, Earnings per Share.